2016
DOI: 10.18632/oncotarget.9469
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation profiles altered by Helicobacter pylori in gastric mucosa and blood leukocyte DNA

Abstract: PurposeTo investigate Helicobacter pylori (H.pylori) associated genome-wide aberrant methylation patterns in gastric mucosa and blood leukocyte DNA, a population-based study was conducted in Linqu County.ResultsA total of 3000 and 386 CpGs were differentially methylated after successful H.pylori eradication in gastric mucosa and blood leukocyte DNA respectively, and 17 were the same alteration trend in the both tissues. The differentially methylated CpGs were located more frequently in promoters or CpG islands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…A large number of DMPs (1,924) associated with H. pylori infection were identified, demonstrating the widespread deregulation of the methylome in normal gastric mucosa infected by H. pylori . A few previous studies have investigated the impact of H. pylori infection on DNA methylation in normal gastric mucosa . However, compared with these works, our study was not limited by sample size nor methylome coverage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of DMPs (1,924) associated with H. pylori infection were identified, demonstrating the widespread deregulation of the methylome in normal gastric mucosa infected by H. pylori . A few previous studies have investigated the impact of H. pylori infection on DNA methylation in normal gastric mucosa . However, compared with these works, our study was not limited by sample size nor methylome coverage.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have conducted DNA methylation analysis in GC tumours and their adjacent tissues using candidate gene or genome‐wide approaches; however, these studies were limited to cancer tissue, and the effects of H. pylori were not considered. Three studies have identified methylation signatures in normal gastric mucosa in response to H. pylori infection, but these involved only several genes or partial DNA methylome coverage or did not include GC patients . Two studies, which tested three candidate genes to identify risk markers for gastric metachronous cancer, were focused on the progression of cancer after excluding the effect of H. pylori infection .…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between HP infection and gastric carcinogenesis has been substantially demonstrated. The carcinogenicity of HP has been well established, involving the injection of CagA by type IV secretion systems [4][5][6][7] or alterations to the DNA methylome [8][9][10][11]. Importantly, several prospective studies had stated that gastric cancer develops only in patients with HP infection [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant methylation of regional promoter CpG islands frequently occurs in H pylori ‐infected gastric epithelia and is accompanied by severe inflammation and atrophy . Blood leukocyte DNA methylation at some tumor‐related genes is a powerful noninvasive biomarker to evaluate the risk of GC . However, the role of the methylation status of tumor‐related genes in blood samples of patients with GC lacks assessment.…”
Section: Discussionmentioning
confidence: 99%